Exploring primordial black holes and gravitational waves with R-symmetric GUT Higgs inflation - Nadir Ijaz; Mansoor Ur Rehman (Physics Letters B)
This study investigates the realization of R-symmetric Higgs inflation within the framework of no-scale-like supergravity, aiming to elucidate the formation of primordial black holes and observable gravitational waves within a class of GUT models. We explore the possibility of an ultra-slow-roll phase in a hybrid inflation framework, where the GUT Higgs field primarily takes on the role of the inflaton. The amplification of the scalar power spectrum gives rise to scalar-induced gravitational waves and the generation of primordial black holes. The predicted stochastic gravitational wave background falls within the sensitivity range of existing and upcoming gravitational wave detectors, while primordial black holes hold the potential to explain the abundance of dark matter. Furthermore, we highlight the significance of the leading-order nonrenormalizable term in the superpotential of achieving inflationary observables consistent with the latest experimental data. Additionally, the predicted range of the tensor-to-scalar ratio, a key measure of primordial gravitational waves, lies within the observational window of future experiments searching for B-mode polarization patterns in cosmic microwave background data.